First-year student’s work and rest balance as an enabler to transition to adult learning - Nemickienė, Živilė; Nemickaite, Emilija (Technium Social Sciences Journal, 2021)
The present research analyses one out of multiple challenges the first-year students face during their transition to academic life, namely, the first-year students’ work and rest balance. The balance, if managed wisely, might become a strong enabler to a successful transition to university life. The study analyses a series of factors, such as the balance of work and rest of the first-year students, skills of time management and the psychological state during the first months at university. The study employs a comparative analysis to evaluate the average hours of work and rest per week of a first-year student comparing with the planned time. The data of students’ work and rest balance was collected from the diary they were asked to record for two months. A focus group was comprised of twenty-five respondents of finance, twelve students of language and three of health science study programs at Lithuanian universities.